Analisis Kasus Rafael Alun Trisambodo Terhadap Kepatuhan Pelaporan SPT Tahun Pajak 2022 - Nosilia Fristiani; Eris Dianawati (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2023)
This study aims to determine the analysis of Rafael Alun Trisambodo's case on the compliance of tax return reporting for Tax Year 2022 for taxpayers registered with KPP Pratama Timika. The research method was carried out using a quantitative descriptive approach which was processed using statistical data analysis for the last three years and the number of taxpayers registered in that time span. Data collection techniques are carried out by means of documentation. The results found from this study are the effect of Rafael Alun Trisambodo's case on the level of compliance with reporting Annual Tax Returns of Taxpayers reported before maturity or on time at KPP Pratama Timika per Type of Submission Media for Tax Year 2022 which decreased by 10.46% from Tax Year 2021 for e-filling delivery media, then for e-form submission media decreased by 36.56% from in Tax Year 2021, Apart from the effects of the Rafael Alun Trisambodo case, there is also a policy from the Government that makes reporting with e-SPT media and manuals drop dramatically. As well as the case of Rafael Alun Trisambodo, it also affects the Compliance Ratio for the submission of Annual Taxpayer Tax Return reporting for the 2022 Tax Year at KPP Pratama Timika which also decreased from 24.88% in the 2021 Tax Year to 20.21% for e-filling delivery media, then for e-form submission media it decreased from 3.51% in the 2021 Fiscal Year to 2.02%, as well as e-SPT and manual submission media from 2.26% in the 2021 Fiscal Year to 0%.